2021
DOI: 10.1111/jonm.13404
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and midwives' experiences with peer‐group clinical supervision intervention: A pilot study

Abstract: Aim This study aimed to evaluate differences in supervisees' understanding of clinical supervision and their perceptions of organisational functioning before and after engaging in peer‐group clinical supervision. Background Protected reflective time allows discussion of complex issues affecting health care. Peer‐group clinical supervision is one model of clinical supervision that could facilitate this, but it is poorly understood. Methods A pre–post intervention pilot study was performed. The intervention was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These networks should be maintained and enhanced, particularly as the Well-being Coordinator role is in its infancy. Recent studies have addressed the success of “peer group supervision”, which facilitates increased confidence in roles (Davis et al, 2022 ), relationship development in a safe space, increased adaptability (McCarthy et al, 2021 ), stress reduction, and enhanced problem-solving skills (Saab et al, 2021 ; Toros & Falch-Eriksen, 2022 ). It is recommended that similar fora are set up so that Well-being Coordinators can meet to support each other, share information and resources, and address challenges they confront as they adapt to their new role.…”
Section: Discussionmentioning
confidence: 99%
“…These networks should be maintained and enhanced, particularly as the Well-being Coordinator role is in its infancy. Recent studies have addressed the success of “peer group supervision”, which facilitates increased confidence in roles (Davis et al, 2022 ), relationship development in a safe space, increased adaptability (McCarthy et al, 2021 ), stress reduction, and enhanced problem-solving skills (Saab et al, 2021 ; Toros & Falch-Eriksen, 2022 ). It is recommended that similar fora are set up so that Well-being Coordinators can meet to support each other, share information and resources, and address challenges they confront as they adapt to their new role.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is accepted that a Trauma Informed approach can mitigate the risk of psychological and moral distress for nurses who are exposed to secondary trauma (Van der Kolk, 2014). Trauma informed approaches, counselling and engagement with clinical supervision or reflective groups are examples of ways to mitigate threats to wellbeing and performance (Appelbaum et al, 2020; Leddie et al, 2022; Mc Carthy et al, 2021). They require leadership and organizational support to succeed (Lake et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Trauma informed approaches, counselling and engagement with clinical supervision or reflective groups are examples of ways to mitigate threats to wellbeing and performance (Appelbaum et al, 2020;Leddie et al, 2022;Mc Carthy et al, 2021). They require leadership and organizational support to succeed (Lake et al, 2019).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…In the absence of such discussions, or where CSA is ignored, van der Zalm et al Another area for support identified by participants was a need for more clinical supervision. The benefits of clinical supervision for nurses are well recognized, with evidence to support the effectiveness of both individual and group approaches (McCarthy et al, 2021;Saab et al, 2021). Indeed, staff who work with survivors of CSA have reported that clinical supervision is essential, and that they would struggle with their work without availing of this support (Wheeler & McElvaney, 2018).…”
Section: Discussionmentioning
confidence: 99%